The Roots of Appalachian Christianity : The Life and Legacy of Elder Shubal Stearns - Sparks, John, 1961- (Book collections on Project MUSE., 2001)
Appalachia's distinctive brand of Christianity has always been something of a puzzle to mainline American congregations. Often treated as pagan and unchurched, native Appalachian sects are labeled as ultraconservative, primitive, and fatalistic, and the actions of minority sub-groups such as ""snake handlers"" are associated with all worshippers in the region. Yet these churches that many regard as being outside the mainstream are living examples of America's own religious heritage.The emotional and experience-based religion that still thrives in Appalachia is very much at the heart of America.